KEMELUT TEOLOGIS: ANTARA KATOLIKISME, MISTISISME DAN PAGANISME DALAM BLESS ME, ULTIMA - Albertine Minderop (Adabiyyāt: Jurnal Bahasa dan Sastra, 2012)
Novelists aspire to universal truths, and assert that people are basically the same in all places and all times. Novelists ultimately look within themselves to find their words and ideas then explore the subjective realm of the self that, though molded by the social and cultural pressures of their own place and time, acquires suppleness through immersion in a deep literary tradition. This research is the analysis of a novel,  Bless Me, Ultima, written by Rudolfo Anaya. The protagonist in this novel  is Antonio, a six-year old boy  who has theological confusion. His mother is very religious, quiet and patient; while  his environment is full of violence, murder, and injustice. Some of  his friends are non-believers and Ultima, a mystical, old woman has a great influence on him. He regards her as a wise person who can give him secure and peaceful feeling. In his way to be grown up and mature, he is asking the existence of God to answer his questions about unpleasant things and the mystery of life. When he thinks God never answers his questions, he turns to paganism – following his friends to worship the golden carp. A tragedy happens to one of the pagans, then he turns to mysticism where he can get peace and secure feeling, though he still calls the name of God. The method of the research used is hermeneutics – the method of interpretation of the literary texts; the approaches used in this research are literature and philosophy.